TINJAUAN HUKUM EKONOMI SYARIAH SANG SESE KERJASAMA PENGEMBALAAN SAPI MASYARAKAT DESA SITEBA KECAMATAN WALENRANG UTARA KABUPATEN LUWU - Mukhtaram Ayyubi (MADDIKA : Journal of Islamic Family Law, 2020)
This articel discusses Sang Sese's Cooperation with Cowherders with the Siteba Village Community, North Walenrang District, Luwu Regency in terms of Sharia Economic Law. This study aims: to find out and understand the implementation of the cooperation agreement between the cow breeder in Siteba Village, North Walenrang District, Luwu Regency in accordance with the mudharabah contract; In order to know and understand the review of Sharia Economic Law on the implementation of the mudharabah contract in the cooperation of the cow breeding partner in Siteba Village, North Walenrang District, Luwu Regency.